Synthesis method and application of novel high-performance atom dispersion hydrogenation catalytic material
By dispersing active metals atomically on the support, the problem of low catalytic activity of existing catalytic materials is solved, efficient methanol synthesis is achieved, and excellent cycle stability is achieved.
Patent Information
- Application Number
- CN202411758079.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-14
AI Technical Summary
The existing catalytic materials for carbon dioxide hydrogenation synthesis of methanol have low catalytic activity, and there are problems such as poor selectivity, low theoretical yield, fast catalyst deactivation, high risk and high cost in industrial applications.
Atomic dispersion hydrogenation catalytic material with low metal load is used to disperse the central atoms of the active metal on the support by adjusting the calcining temperature or electrostatic interaction, thereby improving the catalytic activity and the utilization rate of precious metal atoms.
The methanol yield reached more than 48%, the single-way methanol conversion number reached 12,872, the catalytic activity was significantly improved, and excellent cycle stability was maintained in the cycle application experiment.
Smart Images

Figure CN119425684A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a synthesis method and application of a key catalytic material for coupling carbon dioxide capture and hydrogenation to synthesize green methanol, belonging to the technical field of carbon dioxide capture, utilization and storage, and specifically to a new high-performance atomically dispersed hydrogenation catalytic material for coupling carbon dioxide capture and hydrogenation to synthesize green methanol, a synthesis method thereof and application in hydrogenating carbon-rich liquids such as ethanolamine to synthesize methanol. Background Art
[0002] Since the Industrial Revolution, greenhouse gas emissions, mainly carbon dioxide, have caused a series of ecological and environmental problems such as global warming, which has become a huge challenge facing human sustainable development.
[0003] Carbon capture, utilization and storage (CCUS) technology is a key large-scale decarbonization technology to address climate change. It is also a core technology to achieve sustainable development, carbon recycling and high-value resource utilization in response to the depletion of fossil resources. The potential market value of the entire industry chain exceeds one trillion yuan. Compared with the carbon capture and storage industry, the carbon capture and resource utilization synthesis green chemical new material industry can not only achieve large-scale carbon fixation, but also bring direct economic value, which is a world trend for the development of the chemical new material industry.
[0004] As one of the CCUS technology routes, the production of green methanol from carbon dioxide is widely recognized as a green and sustainable carbon circular economy model in which methanol is used as a basic energy source and chemical. As an important bulk chemical raw material and fuel, methanol can replace fossil raw materials to produce high-value chemicals such as aldehydes, olefins, and aromatics. In addition, compared with methanol synthesis technologies based on coal chemical industry such as coal gas, natural gas, and coke oven gas with high energy consumption and high carbon emissions, carbon capture, utilization, and storage of synthetic methanol is the core of the green and sustainable "methanol" economy and one of my country's strategic emerging green and low-carbon industries.
[0005] The hydrogenation catalytic materials and processes for the hydrogenation of carbon dioxide to synthesize green methanol are the key to the strategic emerging green and low-carbon industry technology. The hydrogenation of carbon dioxide to synthesize methanol is an exothermic and entropy-reducing process. Traditional research and demonstration application projects mainly focus on catalytic hydrogenation to convert carbon dioxide purified by the carbon capture process, which requires high-temperature reaction conditions (>220°C), and has problems such as poor selectivity, low theoretical yield, rapid catalyst deactivation, high risk and high cost. At the same time, carbon dioxide regeneration has high energy consumption, low carbon density, and high pressurized transportation costs and high risks. The catalysts used in industrial demonstrations or applications are mainly Cu / ZnO / Al2O3 developed by Imperial Chemical Industries in 1960 and ZnO-ZrO2 developed by Academician Li Can of Dalian Institute of Chemical Physics. The cost of methanol is relatively high, about 5,000 yuan / ton of methanol, which is much higher than the cost of coal chemical synthesis of methanol (selling price 2,600 yuan / ton of methanol). In comparison, coupling flue gas carbon dioxide capture and catalytic hydrogenation to produce green methanol is to directly catalytically hydrogenate carbon dioxide-rich liquid to synthesize green methanol, while regenerating the carbon capture agent. This can avoid the energy consumption of carbon dioxide regeneration and pressurized transportation, and transporting carbon dioxide-rich liquid by pipeline or tank truck is safer, less costly, and has a high carbon density. It is especially suitable for capturing low-concentration point source or air source carbon dioxide and then transporting it to the hydrogenation plant to synthesize methanol.
[0006] The reported homogeneous hydrogenation catalytic materials can be divided into three categories: monofunctional catalytic materials, M / NH Noyori type bifunctional catalytic materials, and aromatization-dearomatization bifunctional catalytic materials. Among them, monofunctional catalytic materials require an acidic catalytic environment, so they are incompatible with amine-based carbon capture systems. M / NH Noyori type bifunctional catalytic materials use the synergistic effect of NH and metal to activate hydrogen, assist metal hydrogen negative / proton transfer and stabilize the transition state. In addition, aromatization-dearomatization bifunctional catalytic materials use the active protons of benzyl methylene to participate in hydrogen activation and metal hydrogen negative / proton transfer. Therefore, M / NH Noyori type bifunctional catalytic materials and aromatization-dearomatization bifunctional catalytic materials can be used in the amine-based carbon-rich liquid hydrogenation methanol synthesis catalytic reaction to improve the methanol synthesis efficiency. Currently, Ru-MACHO-BH (J.Am.Chem.Soc.2018,140(5):1580-1583.), Ru-PNNN (Chin.J.Che.2018,36(11):1000-1002.), and Ru-CNN (ACS Catal.2023,13(2):927-933) have been successfully applied in the field of homogeneous catalysis for coupled carbon dioxide capture and hydrogenation to methanol. However, due to their low catalytic activity, the maximum methanol conversion number in a single-reactor reaction is 2100, and the separation process of homogeneous catalytic materials increases the process technology and energy consumption, which cannot meet the requirements of industrial application for the time being.
[0007] Heterogeneous catalytic materials have the advantages of easy scale-up synthesis, high stability, and easy separation. In recent years, they have become a new research hotspot and difficulty in the field of coupled carbon dioxide hydrogenation to methanol catalysis. In 2022, the Heldebrant team (Adv. Energy Mater. 2022, 12, 2202369) developed the only heterogeneous catalytic material 5wt% Pt / TiO2 based on formamide intermediates for coupled carbon capture and hydrogenation to synthesize green methanol based on the idea of carrier screening and synergistic optimization of precious metals and carriers. The methanol yield is 11.5% and the single-pass methanol conversion number is 15. However, due to its high precious metal loading, low catalytic activity, and the need to use amine carbon capture agents that have not yet been industrialized, the methanol cost simulated and predicted by combining small-scale continuous test data is significantly lower than the market price of green methanol, but much higher than the cost of coal chemical synthesis methanol.
[0008] Therefore, although catalytic materials for coupling carbon dioxide capture and catalytic hydrogenation to synthesize green methanol have been reported, the catalytic activity is still insufficient to meet the requirements, and there are no research reports on the catalytic system for coupling industrial amine carbon capture and hydrogenation to produce green methanol. Therefore, it is still necessary to research and develop new high-performance catalytic hydrogenation materials. Summary of the invention
[0009] In view of the above-mentioned technical problems, the present invention aims to provide a synthesis method and application of a new high-performance atomically dispersed hydrogenation catalytic material for coupling carbon capture and hydrogenation to synthesize methanol. In the application of coupling carbon capture and hydrogenation to synthesize methanol, the new high-performance atomically dispersed hydrogenation catalytic material of the present invention utilizes low metal loading, adjustment of calcination temperature or electrostatic interaction to enable the active metal center to be atomically dispersed on the carrier, and the methanol yield can reach more than 48%, and the single-pass methanol conversion number reaches 12872, achieving a significant improvement in catalytic activity and precious metal atom utilization. Moreover, after 4 cycles in the cyclic application experiment, the methanol yield can still be maintained at about 48%, and the single-pass methanol conversion number is stable between 12768-13441, showing excellent cycle stability and catalytic activity, and has high application value.
[0010] To achieve the above objectives, the present invention adopts the following technical solutions.
[0011] On the one hand, the present invention provides a new type of high-performance atomically dispersed hydrogenation catalytic material, whose composition is: 0.005-0.5wt% A / B; wherein A is a catalytically active metal, and the catalytically active metal is one or a combination of two of iridium, rhodium, platinum, ruthenium or copper; B is a catalytic material carrier, and the catalytic material carrier is one or a combination of two of cerium oxide, aluminum oxide, titanium oxide, zinc oxide or zirconium oxide.
[0012] On the other hand, the present invention provides a method for synthesizing the novel high-performance atomically dispersed hydrogenation catalyst material, which is characterized in that it comprises synthesizing the novel high-performance atomically dispersed hydrogenation catalyst material under calcination conditions by an equal volume impregnation method or an electrostatic adsorption method on a catalytically active metal and a catalytic material carrier.
[0013] In some embodiments, the equal volume impregnation method comprises the following steps:
[0014] Step a1: adding a chlorate and / or nitrate solution of a carrier metal into an icy hydrochloric acid solution and stirring;
[0015] Step a2: adding the obtained mixture into a distilled aqueous solution of ammonium hydroxide;
[0016] Step a3: adding ammonium hydroxide solution to the mixture to adjust the pH value;
[0017] Step a4: aging the mixture, washing with deionized water, drying, and calcining to obtain a catalytic material carrier 1;
[0018] Step a5: calcining the catalytic material carrier 1 or catalytic material carrier 2 powder obtained in step a4 in air, and then testing its water absorption rate;
[0019] Step a6: preparing a catalytically active metal precursor solution according to the water absorption rate and the catalytically active metal loading;
[0020] Step a7: impregnating with equal volume to obtain a catalytic material precursor;
[0021] Step a8: Place the catalytic material precursor in an oven to dry, and then calcine in air to obtain a high-performance hydrogenation catalytic material.
[0022] In some embodiments,
[0023] The carrier metal is one or a combination of two of cerium, aluminum, titanium, zinc or zirconium;
[0024] The catalytically active metal is one or a combination of two of iridium, rhodium, platinum, ruthenium or copper;
[0025] The catalytically active metal precursor is a chlorate, acetylacetonate and / or nitrate of the catalytically active metal;
[0026] The catalytic material carrier 2 is one or a combination of two of cerium oxide, aluminum oxide, titanium oxide, zinc oxide or zirconium oxide.
[0027] In some embodiments,
[0028] When the carrier metals in step a1 are two combinations, the molar ratio of the two is 1:1-5, preferably 1:3;
[0029] The mass concentration of the hydrochloric acid icy aqueous solution in step a1 is 1-5%, preferably 3%;
[0030] The mass concentration of the distilled aqueous ammonium hydroxide solution in step a2 is 1-5%, preferably 2.5%;
[0031] In step a3, the pH value is 9-12, preferably 10;
[0032] The aging time in step a4 is 4-24 hours, preferably 10-16 hours, more preferably 12 hours;
[0033] The drying temperature in step a4 is 70-100°C, preferably 90°C;
[0034] The drying time in step a4 is 4-16 hours, preferably 6-10 hours, more preferably 8 hours;
[0035] In step a4, the calcination temperature is 350-700°C, preferably 450-550°C, more preferably 500°C;
[0036] The calcination time in step a4 is 2-8 hours, preferably 3-6 hours, more preferably 4 hours.
[0037] In some embodiments,
[0038] In step a5, the calcination temperature is 350-700°C, preferably 450-550°C, more preferably 500°C;
[0039] The calcination time in step a5 is 2-8 hours, preferably 3-6 hours, more preferably 4 hours;
[0040] The heating rate of calcination in step a5 is 3-15°C / min, preferably 3-8°C / min, more preferably 5°C / min;
[0041] In step a6, the catalytically active metal loading is 0.005wt%-0.5wt%, preferably 0.005wt%-0.1wt%, more preferably 0.025wt%, 0.1wt% or 0.5wt%;
[0042] The medium volume immersion time in step a7 is 4-24 hours, preferably 10-16 hours, more preferably 12 hours;
[0043] In step a8, the oven temperature is set at 80-120°C, preferably 100°C;
[0044] The drying time in step a8 is 4-16 hours, preferably 6-10 hours, more preferably 8 hours;
[0045] In step a8, the calcination temperature is 400-1200° C., preferably 400-800° C., more preferably 400° C. or 800° C.;
[0046] The calcination time in step a8 is 2-8 hours, preferably 3-6 hours, more preferably 4 hours;
[0047] The heating rate of calcination in step a8 is 3-15°C / min, preferably 3-8°C / min, more preferably 5°C / min.
[0048] In some embodiments, the electrostatic adsorption method comprises the following steps:
[0049] Step b1: Grind the catalyst material carrier 1 or the catalyst material carrier 3 into powder and dry it in a vacuum oven;
[0050] Step b2: mixing deionized water and ammonium hydroxide solution to dissolve the catalyst material carrier, adjusting the pH value, and obtaining a catalyst material carrier solution;
[0051] Step b3: dissolving a catalytically active metal precursor in deionized water, taking the mixture, adding it to an ammonium hydroxide solution, and adjusting the pH value to obtain a catalytically active metal precursor solution;
[0052] Step b4: adding the catalytically active metal precursor solution to the catalytic material carrier solution prepared in step b2, and stirring;
[0053] Step b5: heating the final mixed solution until it is completely dry to obtain a catalytic material precursor;
[0054] Step b6: calcining the catalytic material precursor in flowing air to obtain a high-performance hydrogenation catalytic material.
[0055] In some embodiments,
[0056] The catalytically active metal is one or a combination of two of iridium, rhodium, platinum, ruthenium or copper;
[0057] The catalytically active metal precursor is a chlorate, acetylacetonate and / or nitrate of the catalytically active metal;
[0058] The catalytic material carrier 3 is one or a combination of two of cerium oxide, aluminum oxide, titanium oxide, zinc oxide or zirconium oxide.
[0059] In some embodiments,
[0060] In step b1, the amount of catalyst material carrier 1 or catalyst material carrier 3 added is 0.5-5 g, preferably 0.5-2 g, more preferably 1 g;
[0061] In step b1, the catalytic material carrier 1 or the catalytic material carrier 3 is a powder of ≤50-150 μm, preferably a powder of ≤75 μm;
[0062] The drying temperature in step b1 is 70-150°C, preferably 90-120°C, more preferably 100°C;
[0063] The drying time in step b1 is 4-16 hours, preferably 6-10 hours, more preferably 8 hours;
[0064] In step b2, the pH value of the catalyst material carrier solution is 10-14, preferably 12-13, more preferably 12.2;
[0065] In step b3, the catalytically active metal precursor is 5-30 mg, preferably 5-15 mg, more preferably 10 mg;
[0066] In step b3, the amount of deionized water is 2-10 mL, preferably 3-6 mL, more preferably 5 mL;
[0067] The mixture in step b3 is 100-500 μL, preferably 200-400 μL, more preferably 300 μL;
[0068] In step b3, the ammonium hydroxide solution is 10-40 mL, preferably 20-30 mL, more preferably 25 mL;
[0069] In step b3, the pH value of the catalytically active metal precursor solution is 10-14, preferably 12-13, more preferably 12.2;
[0070] In step b4, the catalytically active metal precursor solution is 5-30 mL, preferably 20-30 mL, more preferably 25 mL;
[0071] The stirring time in step b4 is 8-24 hours, preferably 12-16 hours, more preferably 12.5 hours;
[0072] In step b5, the heating temperature is 60-100°C, preferably 60-80°C, more preferably 70°C;
[0073] In step b6, the calcination temperature is 300-500°C, preferably 400-500°C, more preferably 400°C;
[0074] The calcination time in step b6 is 2-8 hours, preferably 2-6 hours, more preferably 4 hours;
[0075] The heating rate of calcination in step b6 is 3-15°C / min, preferably 8-12°C / min, more preferably 10°C / min.
[0076] In another aspect, the present invention provides an application of the novel high-performance atomically dispersed hydrogenation catalytic material in coupling carbon capture and hydrogenation to synthesize methanol.
[0077] In some embodiments, the application comprises the following steps:
[0078] (1) Using ethanolamine as the capture solvent, the CO2 carbon-rich liquid was prepared by weighing method:
[0079] Step c1: Add capture solvent 100% ethanolamine or 30% ethanolamine into the reaction bottle;
[0080] Step c2: Bubble CO2 gas at room temperature and stir, take out part of the solution every 5 minutes for weighing and measuring, and prepare CO2 carbon-rich solution;
[0081] (2) Single-pot CO2 carbon-rich liquid hydrogenation to methanol:
[0082] Step d1: The prepared high performance hydrogenation catalyst material is pretreated in situ in a reducing flow of 50 standard cubic centimeters per minute, containing 10% H2 in N2;
[0083] Step d2: In a N2 atmosphere glove box, in a Parr reactor equipped with a thermocouple, a pressure sensor and a reactor controller, add the high-performance hydrogenation catalytic material pretreated in situ in step d1 and the CO2 carbon-rich liquid, and close the reactor;
[0084] Step d3: Take out the reactor, replace it with hydrogen, and then inject hydrogen to a certain pressure;
[0085] Step d4: heating the reaction kettle to react;
[0086] Step d5: After the reaction is completed, the reactor is cooled to room temperature to release the remaining excess gas;
[0087] Step d6: adding n-butanol / tert-butanol as an internal standard to the reaction mixture, and taking a sample for NMR and gas chromatography analysis.
[0088] In some embodiments,
[0089] The reduction temperature in step d1 is 100-140°C, preferably 120-140°C, more preferably 120°C;
[0090] The in-situ pretreatment time in step d1 is 10-24 hours, preferably 10-14 hours, more preferably 12 hours;
[0091] In step d2, the amount of high performance hydrogenation catalyst added is 50-300 mg, preferably 200 mg;
[0092] In step d2, the amount of CO2 carbon-rich liquid added is 3-10 g, preferably 5 g;
[0093] In step d3, the hydrogen pressure is 40-80 bar, preferably 60 bar;
[0094] The reaction temperature in step d4 is 150-200°C, preferably 160-170°C, more preferably 170°C;
[0095] The reaction time in step d4 is 10-24 hours, preferably 10-14 hours, and more preferably 12 hours.
[0096] In some embodiments, the application comprises the following steps:
[0097] (1) Using ethanolamine as the capture solvent, a 6 wt% CO2 carbon-rich solution was prepared by weighing method:
[0098] Step c1: Add 500 mL of capture solvent 100% ethanolamine or 30% ethanolamine into a 1 L reaction bottle;
[0099] Step c2: Bubble CO2 gas at room temperature and stir, take out part of the solution every 5 minutes for weighing and measuring, and prepare 6wt% CO2 carbon-rich solution;
[0100] (2) Single-pot 6wt% CO2 carbon-rich liquid hydrogenation to methanol:
[0101] Step d1: The prepared high performance hydrogenation catalyst material is pretreated in situ in a reducing flow of 50 standard cubic centimeters per minute, containing 10% H2 in N2;
[0102] Step d2: In a N2 atmosphere glove box, in a Parr reactor equipped with a thermocouple, a pressure sensor and a reactor controller, add the high-performance hydrogenation catalytic material pretreated in situ in step d1 and 6 wt% CO2 carbon-rich liquid, and close the reactor;
[0103] Step d3: Take out the reactor, replace it with hydrogen, and then inject hydrogen to a certain pressure;
[0104] Step d4: heating the reaction kettle to react;
[0105] Step d5: After the reaction is completed, the reactor is cooled to room temperature to release the remaining excess gas;
[0106] Step d6: adding n-butanol / tert-butanol as an internal standard to the reaction mixture, and taking a sample for NMR and gas chromatography analysis.
[0107] In some embodiments,
[0108] The reduction temperature in step d1 is 100-140°C, preferably 120-140°C, more preferably 120°C;
[0109] The in-situ pretreatment time in step d1 is 10-24 hours, preferably 10-14 hours, more preferably 12 hours;
[0110] In step d2, the amount of high performance hydrogenation catalyst added is 50-300 mg, preferably 200 mg;
[0111] In step d2, the amount of 6wt% CO2 carbon-rich liquid added is 3-10g, preferably 5g;
[0112] In step d3, the hydrogen pressure is 40-80 bar, preferably 60 bar;
[0113] The reaction temperature in step d4 is 150-200°C, preferably 160-170°C, more preferably 170°C;
[0114] The reaction time in step d4 is 10-24 hours, preferably 10-14 hours, and more preferably 12 hours.
[0115] The beneficial effects of the present invention are:
[0116] The synthesis method of the novel high-performance atomically dispersed hydrogenation catalytic material described in the present invention is simple, reliable, and suitable for industrial production. Moreover, compared with the catalytic performance of the multiphase hydrogenation catalytic material prepared in the previous report, the novel high-performance atomically dispersed hydrogenation catalytic material prepared by the present invention uses low metal loading, adjustment of calcination temperature or electrostatic interaction to enable the active metal center to be atomically dispersed on the carrier in the application of coupling carbon capture and hydrogenation to synthesize methanol, and the methanol yield can reach more than 48%, and the single-pass methanol conversion number reaches 12872, achieving a significant improvement in catalytic activity and precious metal atom utilization. Moreover, after 4 cycles in the cyclic application experiment, the methanol yield can still be maintained at about 48%, and the single-pass methanol conversion number is stable between 12768-13441, showing excellent cycle stability and catalytic activity, and has a high application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0117] Figure 1 XRD characterization spectra of 0.025wt% Pt / TiO2-SEA, 0.025wt% Pt / TiO2-800℃ and 0.025wt% Pt / TiO2-400℃ high performance hydrogenation catalytic materials;
[0118] Figure 2 HAADF-STEM (left picture) and EDX (three pictures on the right) characterization spectra of 0.025wt% Pt / TiO2-800℃ high-performance hydrogenation catalytic material. DETAILED DESCRIPTION
[0119] Example 1: Preparation of CeO2-TiO2 composite support 1Ce-3Ti with Ce / Ti molar ratio of 1 / 3 by improved coprecipitation method
[0120] 18mL (95% wt%, 29.6g, 0.156mol) of TiCl4 was slowly added to 200mL of ice-water solution containing Ce(NO3)3 (15.9g, 0.049mol) and 6mL of concentrated hydrochloric acid, and stirred vigorously. The obtained mixture was dripped into a solution containing 40mL of 25% mass fraction ammonium hydroxide and 400mL of distilled water, and then the pH value of the mixture was adjusted to 10 with 25% mass fraction ammonium hydroxide solution. The mixture was then aged for 12 hours, washed with deionized water, dried at 90°C overnight, and calcined at 500°C for 4 hours to obtain the composite carrier described in the title.
[0121] Example 2: Using commercially available anatase titanium oxide as a carrier, a reference platinum-based hydrogenation catalyst (platinum loading 5 wt%) was prepared by an isovolumetric impregnation method
[0122] Weigh 2.27g of platinum nitrate and 4.75g of titanium dioxide powder. Calcine the titanium dioxide powder in air at 500°C for 4 hours (heating rate 5°C / min), and then test its water absorption. According to the water absorption and platinum loading (5wt%), prepare a platinum nitrate solution, impregnate an equal volume for 12 hours to obtain a catalytic material precursor, put it into an oven at 100°C for 8 hours, and calcine it in air at 400°C for 4 hours (heating rate 5°C / min) to obtain a 5wt% Pt / TiO2-400°C hydrogenation catalytic material.
[0123] Example 3: Using commercially available anatase titanium oxide or a newly synthesized CeO2-TiO2 composite carrier 1Ce-3Ti as a carrier, a high-performance atomically dispersed hydrogenation catalytic material with a platinum loading of 0.5wt%, 0.1wt% and 0.025wt% was prepared by an isovolumetric impregnation method
[0124] Weigh 0.2270g, 0.0454g or 0.0114g of platinum nitrate and 4.75g of titanium dioxide powder, or weigh 0.2270g of platinum nitrate and 4.75g of 1Ce-3Ti powder. Calcine the titanium dioxide powder or 1Ce-3Ti powder at 500°C in air for 4 hours (heating rate 5°C / min), and then test its water absorption. According to the water absorption rate and platinum loading (0.5wt%, 0.1wt% and 0.025wt%), platinum nitrate solution was prepared, and an equal volume was impregnated for 12 hours to obtain a catalytic material precursor, which was placed in an oven and dried for 8 hours at 100°C, and calcined in air at 400°C for 4 hours (heating rate 5°C / min) to obtain high-performance atomically dispersed hydrogenation catalytic materials with platinum loadings of 0.5wt%, 0.1wt% and 0.025wt%, namely 0.5wt% Pt / TiO2-400°C, 0.1wt% Pt / TiO2-400°C, 0.025wt% Pt / TiO2-400°C and 0.5wt% Pt / 1Ce-3Ti-400°C.
[0125] Example 4: Preparation of high performance atomically dispersed hydrogenation catalytic materials with platinum loadings of 0.1 wt% and 0.025 wt% by adjusting the calcination temperature
[0126] Weigh 0.0454g or 0.0114g of platinum nitrate and 4.75g of titanium dioxide powder. Calcine the titanium dioxide powder in air at 500°C for 4 hours (heating rate 5°C / min), and then test its water absorption. According to the water absorption and platinum loading (0.1wt% and 0.025wt%), prepare a platinum nitrate solution, impregnate an equal volume for 12 hours to obtain a catalytic material precursor, put it into an oven at 100°C for 8 hours, and calcine it in air at 800°C for 4 hours (heating rate 5°C / min) to obtain high-performance atomically dispersed hydrogenation catalytic materials 0.1wt% Pt / TiO2-800°C and 0.025wt% Pt / TiO2-800°C with platinum loading of 0.1wt% and 0.025wt%.
[0127] Example 5: Preparation of 0.025wt% Pt / TiO2-SEA high performance atomically dispersed hydrogenation catalytic material by electrostatic adsorption method
[0128] 1g of titanium dioxide was ground, powders finer than 75μm were screened, and dried in an oven at 100℃ for 8 hours. 25mL of deionized water was mixed with 75mL of 25% mass fraction ammonium hydroxide solution to dissolve the titanium dioxide carrier, and the pH of the carrier solution obtained was 12.2. In addition, 10mg of tetraammine platinum nitrate was dissolved in 5mL of deionized water, 300μL was taken and added to 25mL of 25% mass fraction ammonium hydroxide solution to generate a precursor solution with a pH of 12.2. 25mL of tetraammine platinum nitrate solution was slowly injected into the carrier solution for more than 12.5 hours while stirring continuously, and the final total solution volume was 125mL. After slowly adding the precursor solution, the final solution was heated to 70℃ until it was completely dried to obtain a catalytic material precursor. Finally, the catalytic material precursor was raised to 400℃ at a rate of 10℃ / min and calcined in flowing air at 400℃ for 4 hours to obtain 0.025wt% Pt / TiO2-SEA high-performance atomically dispersed hydrogenation catalytic material.
[0129] according to Figure 1 The XRD characterization spectrum analysis shown in the figure shows that no characteristic peaks of Pt metal are seen in the high-performance hydrogenation catalytic materials of 0.025wt% Pt / TiO2-SEA, 0.025wt% Pt / TiO2-800℃ and 0.025wt% Pt / TiO2-400℃, indicating that Pt is highly dispersed. Figure 2 The HAADF-STEM and EDX characterization spectrum analysis shown, combined with the platinum-based single-atom catalysis work of Zhang Tao et al. in 2011 (Nat. Chem., 2011, 3, 634-641), 0.025wt% Pt / TiO2-800℃ high-performance hydrogenation catalytic material presents atomic-level dispersion of metallic Pt.
[0130] Example 6: Single-pot reaction test of the performance of hydrogenation catalyst materials in catalyzing the hydrogenation of carbon-rich liquid to synthesize methanol
[0131] Preparation of 6wt% CO2 carbon-rich solution: Add 500mL of capture solution (100% ethanolamine / 30% ethanolamine) into a 1L three-necked flask, bubble CO2 gas flow into the capture solution at room temperature and stir, take out part of the solution every 5 minutes for weighing and measurement until the solution contains 6wt% CO2.
[0132] In-situ pretreatment of high-performance hydrogenation catalyst materials: Before the single-pot reaction test, the high-performance hydrogenation catalyst materials were in-situ pretreated for 12 hours at 120°C and 5MPa hydrogen atmosphere.
[0133] Hydrogenation experiment: In a 30mL Parr reactor equipped with a thermocouple, a pressure sensor and a reactor controller, high-performance hydrogenation catalytic material (0.2g) pretreated in situ and 6wt% CO2 carbon-rich liquid (5g) were added and sealed in a N2 atmosphere glove box. Then pressurized with H2 (60bar), heated to 170°C and reacted for 12 hours. After the reaction was completed, the reactor was cooled to room temperature and the remaining excess gas was slowly released. n-Butanol / tert-Butanol was added to the reaction mixture as an internal standard, and a small portion of the sample was taken out for nuclear magnetic resonance and gas chromatography analysis to calculate the methanol yield and single-pass methanol conversion number. The results are shown in Table 1.
[0134] The calculation formulas for methanol yield and single-pass methanol conversion number are as follows:
[0135]
[0136] [CH3OH]n is the molar amount of CH3OH after the reaction; [CO2]n is the molar amount of CO2 after capture; M is the relative atomic mass of the catalytically active metal; gcat is the mass of the high-performance hydrogenation catalyst material (gram); [M] is the content of the catalytically active metal (wt%).
[0137] Table 1 Performance test results of high performance hydrogenation catalyst materials
[0138]
[0139] It can be seen from Table 1 No. 1-4 that when the Pt loading is reduced, the catalytic performance is significantly improved. In terms of methanol yield, it can be found that the methanol yield and the Pt loading are in a volcanic relationship. When the loading is 0.1wt%, the methanol yield is the highest, reaching 37.54%. Continue to reduce the loading to 0.025wt%, the methanol yield decreases slightly, but the methanol yield can reach 4.3 times that of the reference hydrogenation catalytic material 5wt% Pt / TiO2-400℃, and more importantly, the single-pass methanol conversion number is increased from 10.5 to 8926.6. The results show that the active metal is dispersed to the atomic level, and its atomic utilization rate is significantly improved, which can significantly improve the catalytic activity. In addition, the present invention also optimizes the hydrogenation catalytic material at the calcination temperature. It can be seen from the comparison of Table 1 No. 4 and 5 that when the calcination temperature is 800℃, the methanol yield is further increased by 1.44 times, reaching 48.41%, and the single-pass methanol conversion number is increased by 1.44 times, reaching 12872.7.
[0140] Example 7: Cyclic application experiment of high performance hydrogenation catalyst material
[0141] The preparation of 6wt% CO2 carbon-rich liquid, in-situ pretreatment of high-performance hydrogenation catalyst materials and hydrogenation experimental operation were the same as those in Example 6. During the cyclic test, 0.025wt% Pt / TiO2-800°C hydrogenation catalyst was obtained by filtration. After in-situ pretreatment, 6wt% CO2 carbon-rich liquid (5g) and hydrogen were added again to synthesize methanol. The results are shown in Table 2.
[0142] Table 2 Test results of cyclic application of high performance hydrogenation catalyst materials
[0143]
[0144] As can be seen from Table 2, after 4 cycles, the methanol yield of the high-performance hydrogenation catalyst material can still be maintained at about 48%, and the single-pass methanol conversion number is stable between 12768-13441, showing high cycle stability and catalytic activity. Therefore, compared with the catalytic performance of the multiphase hydrogenation catalyst material prepared in the previous report, the high-performance hydrogenation catalyst material prepared in the present invention shows excellent cycle stability and catalytic activity, and has high application value.
[0145] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.
Claims
1. A new type of high-performance atomically dispersed hydrogenation catalytic material, the composition of which is: 0.005-0.5wt% A / B; wherein, A is a catalytically active metal, which is one or a combination of two of iridium, rhodium, platinum, ruthenium or copper; B is a catalytic material carrier, which is one or a combination of two of cerium oxide, aluminum oxide, titanium oxide, zinc oxide or zirconium oxide.
2. A method for synthesizing a novel high-performance atomically dispersed hydrogenation catalytic material as claimed in claim 1, characterized in that: The method comprises synthesizing a novel high-performance atomically dispersed hydrogenation catalytic material by using an equal volume impregnation method or an electrostatic adsorption method under calcination conditions to impregnate catalytically active metals and catalytic material carriers.
3. The synthesis method according to claim 2, characterized in that The equal volume impregnation method comprises the following steps: Step a1: adding a chlorate and / or nitrate solution of a carrier metal into an icy hydrochloric acid solution and stirring; Step a2: adding the obtained mixture into a distilled aqueous solution of ammonium hydroxide; Step a3: adding ammonium hydroxide solution to the mixture to adjust the pH value; Step a4: aging the mixture, washing with deionized water, drying, and calcining to obtain a catalytic material carrier 1; Step a5: calcining the catalytic material carrier 1 or catalytic material carrier 2 powder obtained in step a4 in air, and then testing its water absorption rate; Step a6: preparing a catalytically active metal precursor solution according to the water absorption rate and the catalytically active metal loading; Step a7: impregnating with equal volume to obtain a catalytic material precursor; Step a8: Place the catalytic material precursor in an oven to dry, and then calcine in air to obtain a high-performance hydrogenation catalytic material.
4. The synthesis method according to claim 3, characterized in that: The carrier metal is one or a combination of two of cerium, aluminum, titanium, zinc or zirconium; The catalytically active metal is one or a combination of two of iridium, rhodium, platinum, ruthenium or copper; The catalytically active metal precursor is a chlorate, acetylacetonate and / or nitrate of the catalytically active metal; The catalytic material carrier 2 is one or a combination of two of cerium oxide, aluminum oxide, titanium oxide, zinc oxide or zirconium oxide.
5. The synthesis method according to claim 3, characterized in that: When the carrier metals in step a1 are two combinations, the molar ratio of the two is 1:1-5, preferably 1:3; The mass concentration of the hydrochloric acid icy aqueous solution in step a1 is 1-5%, preferably 3%; The mass concentration of the distilled aqueous ammonium hydroxide solution in step a2 is 1-5%, preferably 2.5%; In step a3, the pH value is 9-12, preferably 10; The aging time in step a4 is 4-24 hours, preferably 10-16 hours, more preferably 12 hours; The drying temperature in step a4 is 70-100°C, preferably 90°C; The drying time in step a4 is 4-16 hours, preferably 6-10 hours, more preferably 8 hours; In step a4, the calcination temperature is 350-700°C, preferably 450-550°C, more preferably 500°C; The calcination time in step a4 is 2-8 hours, preferably 3-6 hours, more preferably 4 hours.
6. The synthesis method according to claim 3, characterized in that: In step a5, the calcination temperature is 350-700°C, preferably 450-550°C, more preferably 500°C; The calcination time in step a5 is 2-8 hours, preferably 3-6 hours, more preferably 4 hours; The heating rate of calcination in step a5 is 3-15°C / min, preferably 3-8°C / min, more preferably 5°C / min; In step a6, the catalytically active metal loading is 0.005wt%-0.5wt%, preferably 0.005wt%-0.1wt%; The medium volume immersion time in step a7 is 4-24 hours, preferably 10-16 hours, more preferably 12 hours; In step a8, the oven temperature is set at 80-120°C, preferably 100°C; The drying time in step a8 is 4-16 hours, preferably 6-10 hours, more preferably 8 hours; In step a8, the calcination temperature is 400-1200° C., preferably 400-800° C., more preferably 400° C. or 800° C.; The calcination time in step a8 is 2-8 hours, preferably 3-6 hours, more preferably 4 hours; The heating rate of calcination in step a8 is 3-15°C / min, preferably 3-8°C / min, more preferably 5°C / min.
7. The synthesis method according to claim 2, characterized in that The electrostatic adsorption method comprises the following steps: Step b1: Grinding the catalytic material carrier 1 or the catalytic material carrier 3 synthesized as claimed in claim 3 into powder, and drying it in a vacuum oven; Step b2: mixing deionized water and ammonium hydroxide solution to dissolve the catalyst material carrier, adjusting the pH value, and obtaining a catalyst material carrier solution; Step b3: dissolving a catalytically active metal precursor in deionized water, taking the mixture, adding it to an ammonium hydroxide solution, and adjusting the pH value to obtain a catalytically active metal precursor solution; Step b4: adding the catalytically active metal precursor solution to the catalytic material carrier solution prepared in step b2, and stirring; Step b5: heating the final mixed solution until it is completely dry to obtain a catalytic material precursor; Step b6: calcining the catalytic material precursor in flowing air to obtain a high-performance hydrogenation catalytic material.
8. The synthesis method according to claim 7, characterized in that: The catalytically active metal is one or a combination of two of iridium, rhodium, platinum, ruthenium or copper; The catalytically active metal precursor is a chlorate, acetylacetonate and / or nitrate of the catalytically active metal; The catalytic material carrier 3 is one or a combination of two of cerium oxide, aluminum oxide, titanium oxide, zinc oxide or zirconium oxide.
9. The synthesis method according to claim 7, characterized in that: In step b1, the amount of catalyst material carrier 1 or catalyst material carrier 3 added is 0.5-5 g, preferably 0.5-2 g, more preferably 1 g; In step b1, the catalytic material carrier 1 or the catalytic material carrier 3 is a powder of ≤50-150 μm, preferably a powder of ≤75 μm; The drying temperature in step b1 is 70-150°C, preferably 90-120°C, more preferably 100°C; The drying time in step b1 is 4-16 hours, preferably 6-10 hours, more preferably 8 hours; In step b2, the pH value of the catalyst material carrier solution is 10-14, preferably 12-13, more preferably 12.2; In step b3, the catalytically active metal precursor is 5-30 mg, preferably 5-15 mg, more preferably 10 mg; In step b3, the amount of deionized water is 2-10 mL, preferably 3-6 mL, more preferably 5 mL; The mixture in step b3 is 100-500 μL, preferably 200-400 μL, more preferably 300 μL; In step b3, the ammonium hydroxide solution is 10-40 mL, preferably 20-30 mL, more preferably 25 mL; In step b3, the pH value of the catalytically active metal precursor solution is 10-14, preferably 12-13, more preferably 12.2; In step b4, the catalytically active metal precursor solution is 5-30 mL, preferably 20-30 mL, more preferably 25 mL; The stirring time in step b4 is 8-24 hours, preferably 12-16 hours, more preferably 12.5 hours; In step b5, the heating temperature is 60-100°C, preferably 60-80°C, more preferably 70°C; In step b6, the calcination temperature is 300-500°C, preferably 400-500°C, more preferably 400°C; The calcination time in step b6 is 2-8 hours, preferably 2-6 hours, more preferably 4 hours; The heating rate of calcination in step b6 is 3-15°C / min, preferably 8-12°C / min, more preferably 10°C / min.
10. Use of the novel high-performance atomically dispersed hydrogenation catalytic material as claimed in claim 1 or the novel high-performance atomically dispersed hydrogenation catalytic material prepared by the synthesis method as claimed in any one of claims 2 to 9 in coupling carbon capture and hydrogenation to synthesize methanol.
11. The use according to claim 10, characterized in that: The application comprises the following steps: (1) Using ethanolamine as the capture solvent, the CO2 carbon-rich liquid was prepared by weighing method: Step c1: Add capture solvent 100% ethanolamine or 30% ethanolamine into the reaction bottle; Step c2: Bubble CO2 gas at room temperature and stir, take out part of the solution every 5 minutes for weighing and measuring, and prepare CO2 carbon-rich solution; (2) Single-pot CO2 carbon-rich liquid hydrogenation to methanol: Step d1: pre-treating the high performance hydrogenation catalytic material prepared as claimed in claim 2 or 6 in situ in a reducing flow of 50 standard cubic centimeters per minute, N2 containing 10% H2; Step d2: In a N2 atmosphere glove box, in a Parr reactor equipped with a thermocouple, a pressure sensor and a reactor controller, add the high-performance hydrogenation catalytic material pretreated in situ in step d1 and the CO2 carbon-rich liquid, and close the reactor; Step d3: Take out the reactor, replace it with hydrogen, and then inject hydrogen to a certain pressure; Step d4: heating the reaction kettle to react; Step d5: After the reaction is completed, the reactor is cooled to room temperature to release the remaining excess gas; Step d6: adding n-butanol / tert-butanol as an internal standard to the reaction mixture, and taking a sample for NMR and gas chromatography analysis.
12. The use according to claim 11, characterized in that: The reduction temperature in step d1 is 100-140°C, preferably 120-140°C, more preferably 120°C; The in-situ pretreatment time in step d1 is 10-24 hours, preferably 10-14 hours, more preferably 12 hours; In step d2, the amount of high performance hydrogenation catalyst added is 50-300 mg, preferably 200 mg; In step d2, the amount of CO2 carbon-rich liquid added is 3-10 g, preferably 5 g; In step d3, the hydrogen pressure is 40-80 bar, preferably 60 bar; The reaction temperature in step d4 is 150-200°C, preferably 160-170°C, more preferably 170°C; The reaction time in step d4 is 10-24 hours, preferably 10-14 hours, and more preferably 12 hours.
Citation Information
Cited By
Large-scale synthesized novel high-performance atom dispersion hydrogenation catalytic material as well as preparation method and continuous application of large-scale synthesized novel high-performance atom dispersion hydrogenation catalytic material
CN122124817A